2021
DOI: 10.22438/jeb/42/3(si)/jeb-19
|View full text |Cite
|
Sign up to set email alerts
|

Habitat and edaphic preference of Rafflesia R. Br. plant communities in Royal Belum State Park, Perak, Peninsular Malaysia

Abstract: Aim: To investigate the relationship between the microhabitat conditions and soil physico-chemical characters of Rafflesia plant communities and to determine similarities across Rafflesia habitats in Royal Belum State Park, Perak, Peninsular Malaysia. Methodology: The site of Rafflesia population and its microhabitat condition was collected by referring to the previous studies, in addition to interviewing the related parties. A plot study was constructed in each Rafflesia habitat in Royal Belum State Park, Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Meanwhile, soil texture that comprised of sand, clay and silt did not show any significant differences between the plots (p>0.05). The soil moisture in the study area is slightly higher when compared to the lower soil moisture in Royal Belum State Park (RBSP) (3.81-7.13%) (Nur Hayati et al, 2021). The soil in the study area was found to be less fertile due to low SOM value (Subowo, 2010;Tangketasik et al, 2012) when compared with the findings of Nur Hayati et al, (2021), with 2.30-8.17% and Nasihah (2016) with 2.36-4.19% in Lojing Highlands, Kelantan.…”
Section: Physical Properties Of Soilmentioning
confidence: 81%
See 4 more Smart Citations
“…Meanwhile, soil texture that comprised of sand, clay and silt did not show any significant differences between the plots (p>0.05). The soil moisture in the study area is slightly higher when compared to the lower soil moisture in Royal Belum State Park (RBSP) (3.81-7.13%) (Nur Hayati et al, 2021). The soil in the study area was found to be less fertile due to low SOM value (Subowo, 2010;Tangketasik et al, 2012) when compared with the findings of Nur Hayati et al, (2021), with 2.30-8.17% and Nasihah (2016) with 2.36-4.19% in Lojing Highlands, Kelantan.…”
Section: Physical Properties Of Soilmentioning
confidence: 81%
“…The soil moisture in the study area is slightly higher when compared to the lower soil moisture in Royal Belum State Park (RBSP) (3.81-7.13%) (Nur Hayati et al, 2021). The soil in the study area was found to be less fertile due to low SOM value (Subowo, 2010;Tangketasik et al, 2012) when compared with the findings of Nur Hayati et al, (2021), with 2.30-8.17% and Nasihah (2016) with 2.36-4.19% in Lojing Highlands, Kelantan. A high level of SOM can help improve soil aggregates to reduce soil permeability to water (Zulfahmi et al, 2007).…”
Section: Physical Properties Of Soilmentioning
confidence: 81%
See 3 more Smart Citations